2051. Detection of Candida auris Among Previously Unidentified Yeasts Isolated from Ear Discharge Specimens in Japan. (26th November 2018) - Iguchi, Shigekazu; Mizushima, Ryo; Kamada, Keisuke; Itakura, Yasutomo; Yoshida, Atsushi; Uzawa, Yutaka; Arai, Yuko; Umeyama, Takashi; Miyazaki, Yoshitsugu; Sekizuka, Tsuyoshi; Kuroda, Makoto; Makimura, Kouichi; et al.
Abstract: Background: Candida auris has not been detected since first t report in Japan, despite worldwide reports. We recently reported a second isolate of C. auris (TWCC 58191) from ear discharge in Japan. We re-analyzed unidentified yeast strains. Methods: Over 2, 000 clinical yeast samples were available. Among these, 16 yeast strains isolated from the ear discharge were not identified using conventional method. C. auris was identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and internal transcribed spacer and D1/D2 region sequencing. To determine the minimum inhibitory concentration (MIC), the Clinical and Laboratory Standards Institute broth microdilution method was used. Whole genome sequencing, assembly and error correction was performed (Japanese strains). Average nucleotide identity (ANI) among two Japanese strains and four other strains (India, Pakistan, South Africa) was determined. Our 6 strains and previously reported strains ( n = 126) were mapped to JCM15448 and single nucleotide variants (SNVs) were detected. An SNV-based phylogenetic tree was constructed. Results: Five were identified as C. auris . Our strains exhibited relatively low MICs (Table 1). Japanese strains had susceptibility to nearly all agents. Because all strains were obtained from chronic otitis media, the susceptibility may be explained by a lack of exposure to antifungal agents. JCM15448 was assembled based on 11 contigs. All ANIs were over 99%; therefore, all of these strains are C. auris . A total of 168, 810 SNVs were detected in 133 strains. The SNV-based phylogenetic tree is shown Figure 1. Since independent clusters were observed from strains from each area, it is possible that C. auris emerged independently in different regions worldwide. The SNV-based phylogenetic tree was more effective for the identification of Japanese strains (Figure 2). Conclusion: Despite a general lack of reports, C. auris exists in Japan. Clinicians must consider the potential for C. auris detection from otorrhea samples. A phylogenic analysis separates native strains from each area. During an outbreak, an SNV-based phylogenic tree is suitable for analysis owing to its good identification ability. Disclosures: All authors: No reported disclosures.